2013
DOI: 10.1097/aap.0b013e31828e8a1a
|View full text |Cite
|
Sign up to set email alerts
|

The Myth of the Equiangular Triangle for Identification of Sacral Hiatus in Children Disproved by Ultrasonography

Abstract: In children, using the equiangular triangle to identify the sacral hiatus may be inappropriate because the actual triangle formed by the sacral hiatus and PSISs is not equiangular.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 22 publications
1
16
0
1
Order By: Relevance
“…Although neither was significant, these results suggest that pain is managed equally as well with ultrasound-guided blocks, if not better than the traditional gold standard landmark technique, in patients undergoing circumcision. 36 Koo et al, 33,34 Shin et al, 28 Tachibana et al, 29 Ueda et al 39…”
Section: B (Us Vs Landmark Method)mentioning
confidence: 99%
See 1 more Smart Citation
“…Although neither was significant, these results suggest that pain is managed equally as well with ultrasound-guided blocks, if not better than the traditional gold standard landmark technique, in patients undergoing circumcision. 36 Koo et al, 33,34 Shin et al, 28 Tachibana et al, 29 Ueda et al 39…”
Section: B (Us Vs Landmark Method)mentioning
confidence: 99%
“…33 In another observational study, ultrasound allowed for visualization of the sacral hiatus, which offers benefits relative to the equiangular triangle landmark technique, because the position of the sacral hiatus can vary based on patient age, weight, and height. 36 One study used ultrasound imaging to examine spinal structures and determine the prevalence of spinal dysraphism in children with urogenital anomalies. 34 Children suspected of spinal cord tethering showed a lower level of conus medullaris and thicker filum terminale when compared with the normal group.…”
Section: Neuraxial Anesthesiamentioning
confidence: 99%
“…Identification of surface landmarks and alignment of needle placement to the predicted course of the caudal space is traditional practice when performing caudal anesthesia. The validity of the traditional equiangular triangle surface landmark technique has been questioned however, given its poor ultrasound correlation with the sacral hiatus . Indeed, because of variations in the level of the apex of the sacral hiatus (S2–S5), ultrasound‐guided caudal anesthesia can be a useful adjuvant to the clinician in defining the caudal anatomy.…”
Section: Discussionmentioning
confidence: 99%
“…In a fetal dissection study by Aggarwal et al (23), an equilateral triangle configuration could not be formed in any of the 39 cases (two black lines) as opposed to the pediatric textbooks recommendation (white equilateral triangle) ( Figure 4). An ultrasound study demonstrated that the equilateral triangle is unreliable and the distance between the midpoint of the PSISs and the real sacral hiatus more cephalad than the sacral hiatus predicted by the equilateral triangle method (24). This may be partly explained by relative disproportionate growth of the sacrum during development.…”
Section: Surface Anatomy and The Evidence For A Landmarkguided Approachmentioning
confidence: 99%